Avanços no programa de melhoramento de batata da UFLA visando tolerância ao calor - Patiño Torres, Albania José (2016)
The potato (Solanum tuberosum L.) is one of the most important vegetable in the world and is cultivated in temperate, subtropical and tropical climates. Practically all planted area in Brazil uses seed potato of cultivars from temperate countries, causing low performance particularly due to higher temperatures. Therefore, genetic improvement aimed at obtaining cultivars more adapted to heat stress is essential for this crop in tropical regions. The purpose of this study was to assess the heat tolerance progress in the potato breeding program of the Federal University of Lavras (UFLA) in the period 1996-2016 and to identify clones with better performance than the commercial cultivars for the diverse market segments, both under heat stress and under cool temperatures. Four experiments were planted under different temperature regimes, which assessed 57 clones from UFLAʼs potato breeding program to heat tolerance and five control cultivars: Agata, Asterix, Atlantic, Cupido and Markies. The following traits were evaluated: tuber yield, large tubers yield, tuber dry matter content, duration of the vegetative cycle, percentage of tubers with secondgrowth and/or cracks, tuber bulking period and general tuber appearance. The evaluation of genotypes stability as well as the discrimination between environments was performed using GGE-Biplot (Genotype and GenotypeEnvironment Interaction) method. In conclusion, the UFLAʼs potato breeding program aiming to heat tolerance has generated clones better than commercial cultivars for the different market segments, both under heat stress conditions and cool temperatures. Twenty clones showing heat tolerance and responsiveness to cool temperatures were identified for tuber yield, dry matter content and general tuber appearance; two for the table market, four for the frozen french-fries market and seven for potato chips.